Analysis of the Effect of Waste Bank Program on Empowerment of Poor Women in Kelurahan Sicanang Belawan Medan - Mujahiddin Mujahiddin; Yurisna Tanjung; Efendi Augus (Budapest International Research and Critics University, 2018)
The existence of socio-economic benefits generated from waste savings makes the role of waste banks not only limited to waste management and recycling. But the waste bank is also able to increase participation, skills and changes in the attitude of the poor in waste management, especially women who are always involved in the household scale waste management process. On the basis of this, it is important to see the influence of the waste bank on the empowerment of poor women in Sicanang Belawan, Medan. This study uses several theoretical descriptions and related concepts; Garbage Bank and Community Empowerment Program. This research design uses associative research methods with a quantitative approach. This approach is deliberately chosen because to be able to find out the influence and also the relationship between the waste bank program variables and the empowerment of poor women. In this study, the sampling technique uses Harry King's Nomogram, where the total customers of 10 waste banks are 200 customers. Of the 200 customers taken samples with a 5% error rate. So that the number of samples to be examined is 30 customers. Then, 30 of these customers are evenly distributed to each bank of waste banks. So there are 3 customers to represent each waste bank. The results showed, first; The Waste Bank program partially has a significant influence on the empowerment of poor women. This can be seen from the value of Sig = 0.000 which is smaller than α 0.05. In addition, the R Square value is 0. 472. which means that 47.2% of the variation in the variables of empowerment of women can be influenced by the variables of the waste bank program. Second; there is a positive and strong relationship between the Waste Bank Program and Poor Women's Empowerment of r = 0.687.